Laypersons’ misconceptions as a barrier to understanding plea bargaining’s innocence problem - Hamovitch, Leah (Psychology, crime & law, 2023)
Although the vast majority of criminal cases in Canada and the United States are resolved through plea bargaining, research suggests that the public generally disapproves of this practice. Public disapproval toward plea bargaining may reflect the public’s erroneous belief that all defendants who accept a plea are guilty and should be prosecuted to the fullest extent of the law. At this time, it is unclear whether the public is aware of the fact that innocent defendants also accept plea bargains. We administered an exploratory survey to examine undergraduate students’ (N = 237) and community members’ (N = 259) perceptions of the situational and dispositional factors that are associated with false guilty pleas and exposure to crime/law media programmes. Results demonstrated that both students and community members underestimated the degree to which certain situational (e.g. attorney influence, saving money) and dispositional (e.g. age, compliance) factors can influence innocent defendants’ decisions to plead guilty. Results also demonstrated that greater exposure to crime/law media programmes may help to increase public awareness about false guilty pleas.